Establishment of Adventist education in Chile: The Adventist Schoolof Púa and the Adventist School of Chillán (1906-1922) - Parada Ulloa, Marcos (2018)
The history of the Adventist School of Pua and the Adventist School of Chillándate back to the early twentieth century in Chile. The first school was founded in 1902 with the establishment of the Adventist School of Santiago and in 1906 the Adventist School of Pua was founded, directed by Carlos Krieghoff, whose purpose was the formation of workers, evangelization of the native people of the sector and later to serve as the initiators of Adventist education in Chile.In 1922 the Church decided to transfer the school to the town of Chillán, due to its connectivity and closeness with the capital and with the objective of preparing workers for the Adventist work.